Business judgment rule application in company: a comparison based on the case in Indonesia and Malaysia. (December 2019) - Sudarna,; Najwan, J; Muskibah,; Pratiwi,; Pratiwi, D M
Abstract: This article aims to analyze and compares the business decision in the value of justice in any case of the company losses according to the company law in Indonesia and Malaysia. Narrative review based on the study cases was used to make a comparison and conclusion regarding the problem. Based on several cases in Indonesian and Malaysian court regarding the director and non-director officer's decision that leads to company loss, it has been proven that Indonesia did not implement the protection for the directors even the decision is proven for the sake of the company. This makes the directors and officers became hesitant due to the fear of not having protection against the lawsuit should their decision causing deprivation for the company. Meanwhile, in Malaysia, the court has full protection for the director should their decision were proven for the sake of saving the company. Thus, it can be concluded that Indonesia has not fully implemented the business judgment rule compared to Malaysia.